Contribution of Naturalist Intelligence and Learning Participation toward Students’ Knowledge Competence in Science - Yulianti, Ni Made Karisma; Negara, I Gusti Agung Oka; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2020)
Science competence of students continues to develop because it is influenced by factors of intelligence and participation. Lack of understanding of the importance of student participation in obtaining more optimal learning outcomes is no longer one of the priority factors, so students tend to feel lazy, and find it difficult to express opinions which cause the competence of science knowledge does not increase. This study aimed to analyze the significant effect of naturalist ability on the competence of science knowledge, the significant effect of learning participation on the competence of science knowledge, and the significant effect together of naturalist ability and learning participation on the competence of science knowledge of fourth grade students. This type of research is ex-post facto. The population in this study were all fourth-grade students, amounting to 490 students. The sample was determined by proportional random sampling technique and obtained a total sample of 214 people. Naturalist ability data collection and learning participation were obtained by distributing questionnaires and competence in science knowledge was obtained by recording documents. The data analysis technique used was multiple linear regression analysis. The results showed that there was a significant effect of naturalist ability on the competence of science knowledge with a contribution of 12.68%, there was a significant influence of learning participation on the competence of science knowledge with a contribution of 35.44%, and there was a significant influence on naturalist ability and learning participation. to the competence of science knowledge with a contribution of 48.12%. Based on the results of the study, it can be concluded that naturalist abilities and learning participation contribute to the competence of science knowledge of fourth grade elementary school students